2000
DOI: 10.1046/j.1365-2893.2000.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic hepatitis C genotype IV with interferon–ribavirin combination in Saudi Arabia: a multicentre study

Abstract: Between 1996 and 1997, we conducted a multicentre study to assess the effect of combination therapy of interferon (IFN) + ribavirin on chronic hepatitis C genotype 4. Ninety-seven patients were enrolled. Sixty-eight patients (47 male and 21 female) were non-responders to previous therapy with IFN (Group I). Twenty-nine patients (19 male and 10 female) were new (Group II). Following treatment with IFN, 23% in Group I and 9% in Group II had a sustained biochemical response. Only 12% in Group I and 5% in Group II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 13 publications
6
29
1
Order By: Relevance
“…Because NS5A exists as a quasispecies in vivo (13,16), it is possible that clinical isolates of NS5A may have different IL-8 transactivation activities which may lead to different levels of IL-8 in serum and different responses to IFN therapy. Although HCV genotype was not evaluated in the patients analyzed in this study, the prevalent genotypes in Saudi Arabia are types 4 and 1 (2,19), and similar to what has been observed in U.S. studies, types 1 and 4 tend to be quite resistant to IFN therapy (1,3). In future studies, it will be interesting to explore the relationship between levels of IL-8 in serum, NS5A amino acid sequence, HCV genotype, and virological response to therapy.…”
Section: Hcv Infection and Levels Of Il-8 And Tnf-␣ In Serumsupporting
confidence: 67%
“…Because NS5A exists as a quasispecies in vivo (13,16), it is possible that clinical isolates of NS5A may have different IL-8 transactivation activities which may lead to different levels of IL-8 in serum and different responses to IFN therapy. Although HCV genotype was not evaluated in the patients analyzed in this study, the prevalent genotypes in Saudi Arabia are types 4 and 1 (2,19), and similar to what has been observed in U.S. studies, types 1 and 4 tend to be quite resistant to IFN therapy (1,3). In future studies, it will be interesting to explore the relationship between levels of IL-8 in serum, NS5A amino acid sequence, HCV genotype, and virological response to therapy.…”
Section: Hcv Infection and Levels Of Il-8 And Tnf-␣ In Serumsupporting
confidence: 67%
“…Important differences in the HCV genotype exist among countries with genotype 1b being the most frequent both worldwide and in Spain. However, in some countries other genotypes are more prevalent as, for instance, genotype 4 in West Africa and Middle East [1][2][3][4][5][6][7][8] . HCV-4 infection in the West affects two groups: immigrants from endemic countries and natives infected in their own countries.…”
Section: Introductionmentioning
confidence: 99%
“…46,47,49 50 In a recent study, Al Faleh et al reported a disappointing response rate of only 5% among Saudi genotype 4 CAH patients. 51 Although preliminary, these results may emphasize the role of HCV genotypes even with combination therapy.…”
Section: Combination Therapy: Ifn Plus Ribavirinmentioning
confidence: 79%
“…[32][33][34] Although about 40% of patients achieve response at the end of treatment, patients relapse in almost 50% of cases. Viral genotypes lb and 4 infections seem to be poorly responsive to IFN treatment 16,35 compared to genotypes 1a, 2 and 3.…”
Section: Classification Of Interferons (Ifns)mentioning
confidence: 95%